Implementation of Discovery Learning Models to Improve Student Mastery of Zakat Management Materials In Fiqih Study - Badrudin, Badrudin; Zakariyah, Zakariyah (Chalim Journal of Teaching and Learning, 2023)
Quality education will emerge from schools that have good quality, therefore improving the quality and good learning outcomes. This study discusses the implementation of the Discovery Learning Learning Model to improve Student Mastery in Zakat Management Materials in the Fiqih Study Field in Class VIII Mtsn 6 Pasuruan. The formulation of the problem is how to plan discovery learning models, how to implement discovery learning to improve students' mastery of zakat management materials in the field of Fiqih studies, what are the supporting and inhibiting factors for implementing discovery learning to improve student mastery of zakat management materials in the field of Fiqih studies, in research This includes descriptive research using a qualitative approach. While the data collection techniques in this study used the techniques of observation, interviews, and documentation. While the data analysis technique used is descriptive qualitative. Research result. Discovery learning-based Fiqih learning planning at MTSN 6 Pasuruan was realized in the form of a syllabus along with the development of lesson plans. The lesson plan is designed as a teacher's guide for teaching, what is unique is that in addition to containing competency indicators to be achieved, the lesson plan developed by the teacher is also loaded in full and in detail according to the scenario of the stages of the discovery model. Implementation of Fiqih learning based on discovery learning at MTSN 6 Pasuruan was carried out in accordance with the stages of implementation of the discovery learning model (Stimulation, problem statement, data collection, data processing, generalization). What is different from the discovery model, in general, is the way and innovation teachers in delivering, always updated according to technological developments and collaborating with existing media. This makes students able to complete their discoveries very well. Supporting and Inhibiting Factors Fiqih learning is based on discovery learning using repeating the core material into the subject matter, Providing several questions that are relevant to the material presented.